Modelling and Simulation of the Hybrid System PV-Wind - Bangura, Alpha Alhaji; Errouha, Mustapha; HIHI, Hicham; CHALH, Zakaria (Statistics, Optimization & Information Computing, 2023)
In this paper, we focused on modeling and simulation of a hybrid solar-wind energy system, consisting of a photovoltaic cell and a wind turbine driven by a Permanent Magnet Synchronous Generator (PMSG). The proposed system gives details of the hybrid solar-wind system. In the PV subsystem, there will be a photovoltaic energy subsystem, MPPT controller, and a DC-DC boost converter. The wind turbine subsystem includes a wind turbine energy subsystem, PMSG, and MPPT controller. The MPPT controllers were designed to extract the maximum power regardless of the weather conditions and temperatures. The P and O algorithm is introduced in the MPPT used in the PV energy subsystem and on the control of the machine side converter (MSC). The proposed wind turbine energy subsystem is based on Direct Torque and Flux Control (DTFC). The simulated results are demonstrated to show that the hybrid solar-wind generating system can realize a maximum power point tracking control of wind and solar power to satisfy the energy demand over an extensive range under unpredictable atmospheric conditions. The system has been demonstrated by MATLAB/Simulink and tested for variable weather conditions and temperatures.